2013
DOI: 10.1002/gcc.22099
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations and expression alterations in SMAD3/TGFBR2 genes in oral carcinoma correlate with poor prognosis

Abstract: Transforming growth factor beta (TGF-β) signaling is a pleiotropic cytokine signaling pathway, which controls cellular activities ranging from embryogenesis to apoptosis. Although many molecular alterations in this pathway have been described in cancers, the central point of concern, that is how these alterations influence the treatment outcome, has been addressed to a lesser extent. In this study, we have characterized the alterations of TGF-β-SMAD signaling in 97 oral squamous cell carcinoma (OSCC) samples a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…By using prediction algorithms for the identification of genes targeted by the 4 miRNAs with prognostic power, we observed that almost all miRNAs are predicted to converge on genes belonging to common pathways (Table ). In particular, the most significant predicted pathways are related to epidermal growth factor receptor, Ras, nuclear factor‐kappa B, Stat, Wnt/β‐catenin, transforming growth factor‐beta (TGF‐β), and PI3‐K/AKT/mammalian target of rapamycin (mTOR) pathways, which are involved in the development of HNSCC and of OSCC (eg, “ErbB signaling, TGF‐β, and endocytosis”) . Additional pathways related to cancer phenotype, such as Notch, p53, vascular endothelial growth factor, and mitogen‐activated protein kinase (MAPK) signaling pathways and cell motility (Adherens junction and focal adhesion) were found.…”
Section: Resultsmentioning
confidence: 99%
“…By using prediction algorithms for the identification of genes targeted by the 4 miRNAs with prognostic power, we observed that almost all miRNAs are predicted to converge on genes belonging to common pathways (Table ). In particular, the most significant predicted pathways are related to epidermal growth factor receptor, Ras, nuclear factor‐kappa B, Stat, Wnt/β‐catenin, transforming growth factor‐beta (TGF‐β), and PI3‐K/AKT/mammalian target of rapamycin (mTOR) pathways, which are involved in the development of HNSCC and of OSCC (eg, “ErbB signaling, TGF‐β, and endocytosis”) . Additional pathways related to cancer phenotype, such as Notch, p53, vascular endothelial growth factor, and mitogen‐activated protein kinase (MAPK) signaling pathways and cell motility (Adherens junction and focal adhesion) were found.…”
Section: Resultsmentioning
confidence: 99%
“…For example, out of 97 OSCC patients, mutations of the transforming growth factor β receptor 2 ( TGFBR2 ) gene were noted in 21% of samples, whereas novel Smad family member 3 ( Smad3 ) mutations were identified in only three cases. Accordingly, lower levels of TGFBR2 mRNA were indicative of poor overall survival and poor disease-free survival of OSCC patients [ 78 ].…”
Section: Tgfβ Signaling and Oral Cancermentioning
confidence: 99%
“…20 Homozygous deletion of TGFBR2 has been reported in gastric and pancreatic cancer, 21,22 and alteration of TGFBR2 expression is associated with poor prognosis in several cancers. 23,24 The LRP1B gene encodes a member of the LDL receptor family of lipoprotein receptors that is involved in cholesterol metabolism and T1 T2 T3 T4 T5 T6 T7 T8 T9 T10 T11 T12 T13 T14 T15 T16 T17 T18 T19 T20 T21 T22 T23 T24 T25 T26 T27 Total % T28 T29 T30 T31 T32 T33 T34 T35 T36 T37 T38 T39 T40 T41 T42 T43 T44 T45 T46 T47 T48 atherosclerotic lesion formation. Homozygous deletion of LRP1B has been reported in multiple malignancies, namely esophageal cancer, glioblastoma, and cervical cancer.…”
Section: Discussionmentioning
confidence: 99%